Influence of good health and safety management practices on worker performance - Gonzales Azabache, María Roxana (2022)
The purpose of the research was to determine how good occupational health and safety (OHS) management practices influence the performance of workers in a company in the mining sector in Peru, to evaluate the managerial actions taken by the organization, the understanding of the management of worker performance and involve an alternative way to improve health and safety in the mining industry. It was performed under quantitative research method, non-experimental designs, and explanatory causal models; a representative sample of 103 workers was established workers of the organization was selected, to whom two questionnaires were applied. The findings of the study determined that good management practices in health and safety positively influence the performance of workers (rho=0.859; p-value=0.000). Thus, it was found that the measures taken by the company in the management’s undertaking in actions aimed at improving safety, training activities and the promotion of employee participation in the OHS management system have had a favorable impact on the performance of workers. It is important, from the perspective of good practice, the establishment of the appropriate means and conditions for the performance of work activities, the integration of management into management activities, administrative responsibility and risk assessment.